The effect of abdominal drawing-in manoeuvres and abdominal bracing techniques via telerehabilitation on lumbar repositioning error in seated sedentary participants with chronic low back pain and lumbar instability: a randomised controlled trial - Pongsatorn Saiklang; Thiwaphon Chatprem; Parvinee Saiklang; Rungthip Puntumetakul; Gillian Yeowell (Human Movement)
Purpose Lumbar stabilisation exercise (LSE) is recommended for patients with lumbar instability (LI). Two popular techniques include the abdominal drawing-in manoeuvre (ADIM) and abdominal bracing (AB). These techniques have proven their efficacy in the clinical setting; however, there is no comparable effect when they are conducted via telerehabilitation. To investigate the effects of two LSE techniques, ADIM and AB, delivered via telerehabilitation on lumbar repositioning error (LRPE), numeric rating scale, and transversus abdominis muscle performance in seated sedentary participants with chronic low back pain (CLBP) and LI.